If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 16 = 6x + 9 Reorder the terms: 16 + 5x = 6x + 9 Reorder the terms: 16 + 5x = 9 + 6x Solving 16 + 5x = 9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + 5x + -6x = 9 + 6x + -6x Combine like terms: 5x + -6x = -1x 16 + -1x = 9 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + -1x = 9 + 0 16 + -1x = 9 Add '-16' to each side of the equation. 16 + -16 + -1x = 9 + -16 Combine like terms: 16 + -16 = 0 0 + -1x = 9 + -16 -1x = 9 + -16 Combine like terms: 9 + -16 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 2(6-7x)=-6-8x | | 18-3x+7=-46 | | 15-(8x+5)=6 | | 8+32n=31n+27 | | 1/2x-1=15 | | 1/2x-1=15 | | 34a-2=2a+32 | | -3r-3r=-5r+3 | | 32r^2=20r+63 | | -215=-5(-5x+3) | | 34a=2a+32 | | 4m-7-16m-3= | | 1/3^-3 | | 6n^2-2=2n | | 34a=2a+34 | | -2x-6=6x-14 | | 34a=2a+38 | | 4/5b-6=14 | | 3(x+7)-5=2x+7 | | -8(1+2p)=3p-8 | | (3x-6)(3x+7)= | | 0.3(X+15)+0.6(X+25)=33 | | -12x-17=-98 | | 34a=2a+4 | | u/12+(-8)=-8 | | v=x(10-2x)(3-2x) | | -3(x+7)=8 | | 49r^2=14r+8 | | 4+10s-2=9s+14-3s | | x^3/10-14x=2x^2/5 | | 3x-10-5x=-22 | | -1z+3.33=10 |